Concept of developing a professional outlook of a future doctor based on an integrative approach - L. V. Chichanovskaya; E. A. Evstifeeva; A. V. Solovieva; O. N. Bakhareva; L. A. Murashova; R. N. Chirkov; S. A. Sokolov; O. A. Gavrilova (Кардиоваскулярная терапия и профилактика, 2023)
Modern technification of medical practice reduces the humanistic potential of medicine and reduces the effectiveness of treatment.Aim of the project. To create the concept of training medical personnel based on the synergy of the best spiritual and moral traditions of the past and breakthrough scientific, creative, innovative and educational technologies to graduate a new generation of specialists who meet the modern requirements, able to meet the healthcare challenges and ready to become leaders in the medicine of the future.Results. The experience of implementing such an interdisciplinary scientific direction as medical anthropology was used, which explains the influence of various factors on the health and well-being of both one individual and a group of people and is based on the idea of humanization of medicine. A project of a new teaching concept “Tver Spiral” is proposed, where the main idea is the development of a multifaceted personality of a future doctor from the standpoint of medical knowledge, philosophy of medicine, bioethics, and biopolitics. This combines not only the contribution of fundamental knowledge and digitalization in selected areas of medicine, but also the study of a holistic approach in understanding the psychological causes, consequences and ways of improving the health and well-being of the patient as a whole.